Production of few-layered graphene reinforced copper by powder metallurgy - Borand, Gökce; Akcamli, Nazlı; Uzunsoy, Deniz (Taylor and Francis Ltd., 2024)
Powder metallurgy (P/M) was utilized to produce copper (Cu) matrix composites reinforced with few-layered graphene (FLG), which was produced by electric arc discharge (EAD). The structural and mechanical properties of the composites were investigated depending on the milling time and the graphene content. It was determined in SEM and TEM analyses that FLG was uniformly dispersed in the Cu matrix. Compared to pure Cu, an increase in hardness of approximately 31.8% was provided for 0.3 wt% FLG/Cu composite sintered after 5h of milling. Furthermore, with the addition of FLG, a decrease was observed in the COF values of the composites obtained by 7h milling. Grain refinement is considered a relevant strengthening mechanism for FLG/Cu composites. © 2023 Taylor & Francis Group, LLC.
Keywords: Copper; electric arc discharge; graphene; metal matrix composite; powder metallurgy